Cefoxitin as a carbapenem-sparing antibiotic for infections caused by extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae. Issue 11 (November 2015) - Kernéis, Solen; Valade, Sandrine; Geri, Guillaume; Compain, Fabrice; Lavollay, Marie; Rostane, Hidayeth; Carbonnelle, Etienne; Mainardi, Jean-Luc
Abstract: Background: Cefoxitin has demonstrated in vitro resistance to hydrolysis by extended-spectrum beta-lactamases. Methods: We evaluated the microbiological and clinical efficacy of cefoxitin in 33 patients treated for an infection related to extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E). Clinical and microbiological outcomes were assessed from the initiation of cefoxitin therapy to the latest information available in the patient's medical file. Results: The 33 patients were mainly males ( n = 26), aged 70 years (median, minimum–maximum: 23–93) and main sites of infection were urinary ( n = 23) and catheter-related bloodstream infections ( n = 4). Escherichia coli and Klebsiella pneumoniae were isolated in 19 and 14 subjects, respectively. The clinical outcome was favorable in 30 of 33 patients in the first 48 h after the start of cefoxitin, and in 20 (of 24 evaluable) at the end of follow-up. Six microbiological failures were documented and resistance to cefoxitin emerged in two strains of K. pneumoniae. Conclusions: Cefoxitin could be considered as a carbapenem-sparing antibiotic for some ESBL-E infections, preferentially those related to E. coli .